An exploration of lexical bundles in academic lectures: examples from hard and soft sciences - Kashiha, Hadi; Chan, Swee Heng (The Asian Association of Teachers of English as a Foreign Language, 2013)
Recurrent word combinations that carry out specific function have long captured the attention of many linguists. Referred to as extended collocations,lexical bundles are frequently used in spoken and written discourse, helping to shape meaning and coherence in a text or speech. Frequent use of these bundles is indicative of fluency in linguistic production. In the last two decades, lexical bundles have begun to attract considerable attention in corpus-based research; however, there is still an open question of whether they are different across disciplines in spoken discourse. This study aims to explore how four-word lexical bundles are used in 24 academic lectures of hard and soft sciences taken from the British Academic Spoken English(BASE) corpus to see the possible variations in their frequency, structure and function. The present research also attempts to discover the manifestation of the identified bundles in introduction, body and closing sections of the lectures. Findings revealed some marked variations across the two divisions;in that, lecturers in each division appeared to apply different structures and functions in the use of lexical bundles in order to convey their message, so as to be as comprehensive as possible for the learners.